Comparative transcriptional and co-expression network analysis of two upland cotton accessions with extreme phenotypic differences reveals molecular mechanisms of fiber development - He, Jiasen; Xu, Zhongyang; Azhar, Muhammad Tehseen; Zhang, Zhen; Li, Pengtao; Gong, Juwu; Jiang, Xiao; Fan, Senmiao; Ge, Qun; Yuan, Youlu; Shang, Haihong (Frontiers in Plant Science, 2023)
Upland cotton (Gossypium hirsutum) is the main source of natural fiber in the global textile industry, and thus its fiber quality and yield are important parameters. In this study, comparative transcriptomics was used to analyze differentially expressed genes due to its ability to effectively screen candidate genes during the developmental phases of cotton fiber. However, research using this method is limited, particularly on fiber development. The aim of this study was to uncover the molecular mechanisms underlying the whole period of fiber development and the differences in transcriptional levels. Two accessions of upland cotton with extreme phenotypic differences, namely EZ60 and ZR014121, were used to perform RNA-seq on fiber samples from different fiber development stages. The results identified the 704/1052, 376/476, 141/355, 269/259, 761/702, and 586/847 up/down-regulated differentially expressed genes (DEGs) at 0, 5, 10, 15, 20, and 25 days post-anthesis (DPA), respectively. Similar expression patterns of DEGs were monitored using short time-series expression miner (STEM) analysis, and associated pathways of DEGs within profiles were investigated. In addition, weighted gene co-expression network analysis (WGCNA) identified five key modules in fiber development and screened 20 hub genes involved in the development of fibers. Through the annotation of the genes, it was found that the excessive expression of resistance-related genes in the early fiber development stage affects the fiber yield, while the sustained expression of cell elongation-related genes is critical for long fibers. This study provides new information that can be used to improve fibers in newly developed upland cotton genotypes.